Inovasi Pembelajaran Berbasis Paper Quilling untuk Menumbuhkan Imajinasi dan Kreativitas Anak Usia Dini - Ahmad Aly Syukron Aziz Al Mubarok; Erna Budiarti (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2025)
The creativity and imagination of early childhood need to be developed in a directed manner as an essential provision for facing future challenges. One of the efforts that can be made is through art activities using paper quilling media. This study aims to identify the form of learning innovation based on paper quilling and its application in fostering imagination and creativity among Group B children at RA Nurul Huda An-Nur Tunggalpager Pungging Mojokerto. This research is a Classroom Action Research (CAR) employing the Kemmis and Taggart model, conducted in two cycles. The subjects of the study were 14 children aged 5–6 years. Data were collected through interviews, observations, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results of the study indicate that: (1) Learning innovation based on paper quilling was carried out through activities such as creating caterpillar shapes in cycle I and butterfly shapes in cycle II, which successfully stimulated imagination and enhanced children's creativity. (2) There was an improvement in children’s creativity from 60.27% in the pre-cycle, to 76.79% in cycle I, and further increased to 83.48% in cycle II. (3) The effective use of paper quilling media was implemented through clear and repeated explanations and demonstrations, providing opportunities for independent exploration, and creating a pleasant and supportive learning atmosphere.